Analisis Implementasi Undang-Undang Perlindungan Anak oleh Komisi Perlindungan Anak Indonesia (Studi Kasus Penganiayaan Anak di Daycare Depok) - Rumahlatu, Alvaro; Cahyo, Cahyo (Neolectura, 2025)
A child is an individual who has not yet reached adulthood and requires guidance and protection from both parents and society, in accordance with Law Number 35 of 2014 on Child Protection. Child protection is an effort to ensure that children's rights are optimally fulfilled within their social environment, including protecting them from violence or abuse. Child abuse, whether physical or emotional, has significant negative impacts on a child's development, which can hinder their growth. This study examines a case of child abuse that occurred at Wensen School daycare in Depok, where two toddlers, MK and HW, were victims of abuse by their caregiver, Meita Irianty. This research uses a normative juridical method with a qualitative approach to explore child protection regulations in Indonesia, including the Child Protection Law and the role of the Indonesian Child Protection Commission (KPAI). The findings show that such abusive actions can be subjected to legal sanctions under Article 80, Paragraphs (1) and (2) of Law No. 35 of 2014, highlighting the importance of KPAI's role in protecting children's rights and ensuring justice for the victims. This study aims to provide an overview of child protection against abuse and the importance of law enforcement to ensure children's rights are protected.